PROCESO DE NOMINA Y RECURSOS HUMANOS EN LA COMPAÑÍA BANAROYAL DE LA PARROQUIA SAN JUAN - BALDEON PAREDES, JORGE LUIS (2018)
The banana producing companies have a large proportion of labor from our province of Los Ríos. Currently the banana farms face a series of problems that are affecting their profitability, the effects of pests, climate, informality at the time of hiring the Human Talent causes certain specific positions in the organizational gear become critical at the time of a Selection of personal